KAJIAN DAN STRATEGI PENERAPAN ADAPTIVE REUSE PADA BANGUNAN DI KAWASAN HERITAGE JALAN GAJAH MADA DENPASAR, BALI. - IDA BAGUS GEDE PARAMA PUTRA; NI PUTU RATIH PRADNYASWARI ANASTA PUTRI (GANEC SWARA, 2024)
This approach has been widely adopted in many countries around the world and has been the subject of much research and discussion. One of the key understandings around Adaptive reuse is the balance between managing the historical and cultural significance of a building and making it functional and fit for its new use. This can involve changes to the building's physical structure or design, which may be necessary to accommodate new uses, but which also have the potential to compromise its historical integrity. There is also often a tension between the desire to own a building and the need to make it financially viable, as the costs of adapting existing structures to new uses can be significant. Another issue that has been debated in the context of Adaptive reuse of buildings is the role of government and the private sector in spending on and supporting such projects. Some argue that the public sector should play a more active role in promoting and supporting Adaptive reuse, especially for projects involving important historic buildings. Others argue that the private sector should take the lead, with government support in the form of regulations and financial incentives. This research is entitled "Study and Strategy for Implementing Adaptive reuse in Heritage Area Buildings at Jalan Gajah Mada Denpasar, Bali". This study will discuss the various strategies used in changing the function of buildings by considering the concepts and principles of Adaptive reuse. This aims to provide guidelines for implementing and planning development in the Gajah Mada heritage area. The results obtained are that one of the case studies in Gajah Mada obtained an ARP result of 67.3% which is classified as moderate with high potential for Adaptive reuse and the existence of 6 intervention approaches namely Umbrella, New Interior, New Face, Parasite, Bridge and Transition. Such can be a strategy in building planning in the Gajah Mada Heritage Area.